Candidate Species for Florida Aquaculture: Pigfish, Orthropristis chrysoptera - Eric J. Cassiano; Cortney L. Ohs; Jeff E. Hill (EDIS)
FA160, a 6-page illustrated fact sheet by Eric J. Cassiano, Cortney L. Ohs, and Jeff E. Hill, describes this member of the grunt family that is rated as a top species for baitfish aquaculture — general description, geographic distribution and habitat, natural history, and culture techniques. Includes references. Published by the UF School of Forest Resources and Conservation Program in Fisheries and Aquatic Sciences, December 2009.